Clinical Features and Outcome of SARS-CoV 2 Virus Infection in Patients with Autoimmune Diseases - Perveen, Shahida; Salim, Babur; Faisal, Mohammad Jamal; Samreen, Saba (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To evaluate the clinical features, outcome and poor prognostic factors of COVID-19 in rheumatic disease patients.Study Design: Cross-sectional study.Place and duration of Study: Department of Rheumatology, Fauji Foundation Hospital, Rawalpindi, from Mar to Sep 2020.Methodology: The study included rheumatic disease patients with COVID-19. Patients' age, gender, smoking status; details of rheumatic disorder; method of COVID-19 diagnosis, treatment and outcomes were recorded.Results: The study included 46 patients. Overall mortality rate was 23.8%. The most common symptoms were fever (35, 83.3%), cough (26, 61.9%) and myalgia (23, 54.8%). Dyspnea was associated with mortality (p=0.013), ICU admission (p